2014
DOI: 10.1098/rspb.2013.3159
|View full text |Cite
|
Sign up to set email alerts
|

Wet climate and transportation routes accelerate spread of human plague

Abstract: Currently, large-scale transmissions of infectious diseases are becoming more closely associated with accelerated globalization and climate change, but quantitative analyses are still rare. By using an extensive dataset consisting of date and location of cases for the third plague pandemic from 1772 to 1964 in China and a novel method (nearest neighbour approach) which deals with both short-and long-distance transmissions, we found the presence of major roads, rivers and coastline accelerated the spread of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 42 publications
3
68
0
1
Order By: Relevance
“…In turn, 1.IN3 is the last known population that branched off before 1.ORI, which spread globally to cause the ongoing Third Pandemic from Hong Kong in 1894. The plague epidemic in Hong Kong is linked by epidemiological data from the nineteenth century to Yunnan province [51], which was the sole source of 1.IN3.…”
Section: (A) Populations and Phylogenymentioning
confidence: 99%
“…In turn, 1.IN3 is the last known population that branched off before 1.ORI, which spread globally to cause the ongoing Third Pandemic from Hong Kong in 1894. The plague epidemic in Hong Kong is linked by epidemiological data from the nineteenth century to Yunnan province [51], which was the sole source of 1.IN3.…”
Section: (A) Populations and Phylogenymentioning
confidence: 99%
“…), and these factors are closely connected with each other. Yet, although the relationship between climatic factors and the dynamics of disease has been studied frequently [11][12][13][14][15], this is seldom done within the context of a full trophic web, whether via bottom-up (e.g. resource limitation) or top-down pathways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the Justinian, which started in AD 541, the Black Death in AD 1347 and the Third Pandemic in AD 1772) [15,16]. Plague is still active in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…New Mexico, Colorado, Arizona, Utah) perhaps further eastward or toward higher latitudes and/or even higher altitudes [112]. Other, recent studies, demonstrated that environmental factors such as high levels of precipitation and flooding events resulted in increased spread velocity of plague in China and Vietnam [116,117]. The effects of global climate change have been previously described in great detail for many other vector-borne diseases, such as malaria and dengue fever [118,119] considering this evidence, it would be reasonable to assume that climate change can similarly affect the spread and dissemination of plague within the vector and rodent population, ultimately affecting the occurrence of plague within the human population as well.…”
Section: Natural Factors Contributing To Outbreaks: Climate Change Anmentioning
confidence: 99%